Compósitos magnéticos formados por estruturascarbonáceas sobre matrizes inorgânicas paratratamento de efluentes - Bruno Rocha Santos Lemos (2015)
In this work, magnetic carbonaceous nanostructured composites were developed using Chemical Vapor Deposition (CVD) process and two inorganic supports: synthetic (MgO) and natural (chrysotile). Further, the obtained composites were tested for environmental applications in the treatment of wastewater. Chapter 1 provides a literature review on the process of obtaining the magnetic carbonaceous composites, followed by a brief study of environmental applications proposed in this work. A detailed description of reagents, equipment used and methodology applied in the work is shown in Chapter 2. Chapter 3 shows the synthesis of magnetic carbonaceous composites, obtained using a synthetic matrix (MgO), were characterized by RTP, TPCVD, CHN, TG/DTG, Mössbauer, XRD, Raman, SEM, TEM, EDS, adsorption/desorption of N2 and magnetization measurements. The influence of the molybdenum on the material was investigated in bimetallic catalyst systems of Fe/Mo impregnated on the surface of MgO to grow the carbon structures using methane as the carbon source. Chapter 4 shows the synthesis of magnetic carbonaceous composites, obtained using a natural matrix (chrysotile), were characterized by CHN, TG/DTG, Mössbauer, XRD, Raman, SEM, EDS, adsorption/desorption of N2 and magnetic measurements. The influence of metal catalyst used (Fe or Co) on the CVD process using different temperature (600-900 ° C) was investigated for the production of carbonaceous structures using ethanol as carbon source. Finally, Chapter 5 shows tests for environmental applications in the treatment of wastewater. In general, the obtained composites showed good potential for waste remediation, i.e., (i) breaking the emulsion (ii) turbidity removal of a real effluent from biodiesel production process, and (iii) the color removal from aqueous solutions of methylene blue.